Gymnosporia swazica (Celastraceae), a new species from southern Africa - Jordaan, Marie; van Wyk, Abraham E. (Phytotaxa, 2015)
Gymnosporia swazica, a new restricted-range southern African species, is described and illustrated here. Known from only a few localities in Swaziland and bordering parts of South Africa (Mpumalanga and northeastern KwaZulu-Natal), G. swazica grows as an understorey shrub or small tree in forest, often among granite boulders. Diagnostic characters for G. swazica include chartaceous leaves, usually shorter than 25 mm, 3-valved capsules usually 6–7 mm long, which are smooth, green turning yellow, and a white aril partially covering the brownish seed. Its closest relative appears to be G. buxifolia (capsules rugose, mottled white-and-brown), one of the most widespread members of the genus in southern Africa, but it can also be confused with G. maranguensis (capsules red, 2-valved) and G. harveyana (capsules pink to red, 3-valved; aril orange, completely covering the seed).